2019
DOI: 10.1177/1179069519829040
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Neurogenic Aging in the Adult Mouse Subventricular Zone

Abstract: In the adult rodent brain, the continuous production of new neurons by neural stem/progenitor cells (NSPCs) residing in specialized neurogenic niches and their subsequent integration into pre-existing cerebral circuitries supports odour discrimination, spatial learning, and contextual memory capabilities. Aging is recognized as the most potent negative regulator of adult neurogenesis. The neurogenic process markedly declines in the aged brain, due to the reduction of the NSPC pool and the functional impairment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 93 publications
(188 reference statements)
0
29
0
Order By: Relevance
“…Typical aging hallmarks such as genomic instability, telomere shortening, metabolic dysregulation, cellular senescence, stem cell exhaustion, and decreased neurogenesis are observed in the brain and affect a broad range of cellular functions [2], thereby leading to impaired tissue homeostasis and regeneration. a primary reason for this impaired tissue homeostasis and regeneration is age-related exhaustion of tissue-specific stem cells, a process observed in various organs [3][4][5], including the mammalian brain [6][7][8][9][10]. Although prominent age-associated changes, including decreased neurogenesis and changes in the lateral ventricle choroid plexus [11][12][13], have Cells 2020, 9, 2 of 25 been detected in the aging mammalian brain, comparisons of neural stem cell transcriptomes have revealed a remarkably small set of differentially regulated transcripts, which are largely associated with cell cycle regulation, neuronal differentiation, and inflammation [10,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Typical aging hallmarks such as genomic instability, telomere shortening, metabolic dysregulation, cellular senescence, stem cell exhaustion, and decreased neurogenesis are observed in the brain and affect a broad range of cellular functions [2], thereby leading to impaired tissue homeostasis and regeneration. a primary reason for this impaired tissue homeostasis and regeneration is age-related exhaustion of tissue-specific stem cells, a process observed in various organs [3][4][5], including the mammalian brain [6][7][8][9][10]. Although prominent age-associated changes, including decreased neurogenesis and changes in the lateral ventricle choroid plexus [11][12][13], have Cells 2020, 9, 2 of 25 been detected in the aging mammalian brain, comparisons of neural stem cell transcriptomes have revealed a remarkably small set of differentially regulated transcripts, which are largely associated with cell cycle regulation, neuronal differentiation, and inflammation [10,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, NSPCs of the developing brain, such as those located in the ventricular and subventricular zones (VZ/SVZ) of the foetal cerebral cortex and in the VZ/SVZ lining the lateral ventricle in the neonatal brain, are generally highly proliferative and broadly sensitive to IR-induced apoptosis, but those NSPCs that survive irradiation resume proliferation and repopulate the NSPC niche [22][23][24][25] . In contrast, NSPCs of the adult VZ/SVZ niche can exist in an actively proliferating or in a quiescent status 34 . The former subpopulation is radiosensitive and responds to IR by undergoing apoptosis or terminal differentiation, in either case depleting the proliferating NSPC pool; the latter subpopulation is radioresistant and responds to IR by entering the cell cycle and replenishing the proliferating NSPC pool, although the response was shown to depend on the total dose and the dose fractionation scheme that were applied 22,[35][36][37][38][39] .…”
Section: X-ray Irradiation Of Mouse Cortex Nspc Cultures Causes a Tramentioning
confidence: 99%
“…In the case of NSPCs, several studies have investigated their response to IR both in vivo and in vitro, reporting heterogeneous and even contradictory findings. Notably, in vivo analyses in rodents have suggested that the specific response of NSPCs to IR-dependent DNA damage may depend, at least in part, on the age of the animal, possibly due to the known age-associated changes in the NSPC population occurring between foetal and adult stages 33,34 . In particular, NSPCs of the developing brain, such as those located in the ventricular and subventricular zones (VZ/SVZ) of the foetal cerebral cortex and in the VZ/SVZ lining the lateral ventricle in the neonatal brain, are generally highly proliferative and broadly sensitive to IR-induced apoptosis, but those NSPCs that survive irradiation resume proliferation and repopulate the NSPC niche [22][23][24][25] .…”
Section: X-ray Irradiation Of Mouse Cortex Nspc Cultures Causes a Tramentioning
confidence: 99%
“…In the following sections, we will focus on the key age-related molecular changes revealed in specific cell types and regions of the human brain. Recent studies using mouse models to analyze the genome-wide transcriptomic and epigenomic modifications occurring in NSPCs of the aging neurogenic niches have been reviewed elsewhere [12]. [15], DNA methylation [19], and histone H3 lysine 9 acetylation (H3K9ac) [18] datasets from dorsolateral prefrontal cortex (DLPFC) postmortem samples of longitudinal cohorts of human subjects of different ages.…”
Section: Molecular Profiling Of Aged Brain Cells: Insights From Genommentioning
confidence: 99%
“…Finally, aging has a major impact on the generation of new neurons in the adult brain. At least in rodents, in which adult neurogenesis has been best characterized, a sharp age-dependent drop in the production of new neurons is detectable at the level of both of the main adult neurogenic niches, the subventricular zone (SVZ), flanking the lateral ventricles, and the hippocampal subgranular zone (SGZ) [11,12]. Thus, aging can hinder the remodelling of neural circuits by affecting synaptic connectivity and the integration of new neuronal elements, leading to a progressive decline in the functional plasticity of the brain and in cognitive abilities.…”
Section: Introductionmentioning
confidence: 99%